PENGEMBANGAN STRATEGI PEMBELAJARAN BAHASA DAN SASTRA UNTUK MENINGKATKAN KEMAMPUAN BERPIKIR TINGKAT TINGGI (HOTS) - Eka Sartika; Zilfa Achmad Bagtayan; Munkizul Umam Kau (JURNAL PENDIDIKAN DAN KEGURUAN, 2026)
This study aims to analyze and develop effective learning strategies in language and literature education to enhance students’ Higher Order Thinking Skills (HOTS). Using a qualitative approach through library research, this study synthesizes recent scholarly works from reputable international journals indexed in Scopus published within the last five years. The analysis focuses on identifying key strategies, challenges, and research gaps in implementing HOTS-oriented learning in language and literature classrooms. The findings reveal that conventional teacher-centered approaches remain dominant and are insufficient to foster higher-level cognitive skills such as analysis, evaluation, and creation. In contrast, constructivist learning strategies—such as Problem-Based Learning, Project-Based Learning, and critical literacy approaches—demonstrate significant effectiveness in promoting HOTS. Furthermore, integrating digital technologies, including interactive media and digital storytelling, enhances student engagement and supports the development of critical and creative thinking skills. However, the study also identifies several challenges, including limited teacher competency in designing HOTS-based instruction, inadequate learning resources, and constraints related to curriculum implementation. Addressing these issues requires a comprehensive and integrative instructional model that combines critical literacy, project-based learning, and digital technology. This study contributes to the existing literature by proposing a holistic, context-based framework for language and literature learning that aligns with 21st-century educational demands. The findings are expected to provide practical implications for educators and policymakers in improving the quality of learning and fostering students’ higher-order thinking skills in a globalized educational context.